IDENTIFICATION OF ORGANIC COMPOUNDS AS CARBOHYDRATES AND CHEMICALS CONTAINED IN THEM - Fitriana Maod; Fitrawati Dukalang; Ni Luh Arwati (Journal of Health, Technology and Science (JHTS), 2022)
This study aims to observe the structure of some carbohydrates through their reaction properties with multiple test reagents and know and understand various carbohydrate tests. Research methods used Research methods used are analytics with experimental design (pre experimental), Object of research is milk, honey, sago, flour and amylum. Then to five samples each added with NaOH, HCL, Aquades to find out if the five samples contain carbohirat or not. The results showed that Carbohydrates are nutrients in the form of organic compounds consisting of carbon atoms, hydrogen, and oxygen used as energy-forming materials. In this carbohydrate study, an iodine test was conducted to prove the presence of carbohydrate content in 5 samples of foodstuffs, namely iodine test on sago, honey, amylum, flour and milk. In the first experiment milk added NaOH, HCL, aquades the result did not change the layer and color, then the second experiment on honey in the pond NaOH, HCL, Aquades the result is two layers and the change of color to blackish yellow, then the third experiment on flour added NaOH, HCL, Aquades the result there are two layers and discoloration in each organic compound mixed in the sample, next experiment to the fourth on sago added NaOH, HCL,